(untitled) (Journal of the College of Basic Education, 2023)
The study of Arab Muslim historians is one of the most important historical studies , as it reveals an important link in the episodes of the nation intellectual heritage , as it defines features of arab Islamic history and then this study consolidates the approach of historical research . The importance of this study comes Maghltay considered one of the most prominent arab muslim scholars and thinker in the eighth century AH , and who in varios scientific fields , including his book ` al tarajim al sakita men ketab tahtheb al kamal ` the subject of our study .